The effect of steroid hormones on the mRNA expression of oct4 and sox2 in uterine tissue of the ovariectomized mice model of menopause - Marzieh Davoudi; Saeed Zavareh; Mohammad Taghi Ghorbanian; Seyed Hassan Paylakhi; Seyed Reza Mohebbi (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: The uterus is a dynamic tissue responding to hormonal changes during reproductive cycles. As such, uterine stem cells have been studied in recent years. Transcription factors oct4 and sox2 are critical for effective maintenance of pluripotent cell identity. Objective: The present research evaluated the mRNA expression of oct4 and sox2 in the uterine tissues of ovariectomized mice treated with steroid hormones. Materials and Methods: In this experimental study, adult virgin female mice were ovariectomized and treated with estradiol 17β (E2), progesterone (P4), and a combination of E2 and P4 (E2 & P4) for 5 days. Uterine tissues were removed, and immunofluorescent (IF) staining and quantitative real-time PCR of oct4 and sox2 markers were performed. Results: IF showed oct4 and sox2 expression in the uterine endometrium and myometrium among all groups. The mRNA expression of oct4 (p=0.022) and sox2 (p=0.042) in the E2-treated group significantly were decreased compared to that in the control group. By contrast, the mRNA expression of oct4 and sox2 in the P4 (p=0.641 and 0.489 respectively) and E2 & P4-treated groups (p=0.267 and 0.264 respectively) did not show significant differences compared to the control group. Conclusion: The results indicate ovarian steroid hormones change the expression of oct4 and sox2 in the mice uterine tissues, which suggest the involvement of steroid hormonal regulation in uterine stem cells.